Near-miscible supercritical CO2 injection in oil-wet carbonate: A pore-scale experimental investigation of wettability state and three-phase flow behavior. (December 2021) - Qin, Ziqiang; Arshadi, Maziar; Piri, Mohammad
Abstract: Near-miscible supercritical CO 2 ( scCO 2 ) injection and its underlying pore-scale physics were experimentally investigated in an oil-wet carbonate rock at elevated temperature and pressure conditions using X-ray microtomography. The results of in situ contact angle measurements yielded direct evidence showing that the scCO 2 injection triggered a wettability reversal process resulting in reduced oil-wetness. As the scCO 2 injection progressed, we observed a distinct wettability state where the wetting preference of the solid to the scCO 2, oil, and brine phases was similar due to the wettability reversal. Consequently, pore sizes neither dictated any preferential invasion order nor restricted the displacement efficiency of the injection process. Furthermore, we identified a type of spreading system where spreading oil layers formed but did not exist globally across the pore space between the scCO 2 and brine phases. Gaussian curvature analysis showed that the scCO 2 and oil phases were well-connected at the early stage of the scCO 2 injection, whereas brine connectivity was relatively poor. As the injection continued, brine connectivity was improved due to the wettability reversal effect. Moreover, displacement events including double and multiple displacements were identified and discussed. They included a variety of events that had scCO 2 as the first phase and oil and brine as the subsequent phases. The diversity and affordability of such displacements were much higher than those previously observed during N2 injection in oil-wet systems where mostly gas-to-oil-to-brine double displacements took place. The interplay of scCO 2 -oil miscibility, the distinctive wettability state, favorable fluid connectivity, and frequent double/multiple displacements resulted in an exceptional displacement efficiency during near-miscible scCO 2 injection. Highlights: A distinct wettability state for three-phase flow in porous rock is identified. We identify a type of spreading behavior where oil layers formed but did not globally exist. We probe the diversity and affordability of double and multiple displacements under varying wettability conditions. Miscibility and connectivity of fluids are in situ examined at pore scale.